Secretion Systems in Gram-Negative Bacterial Fish Pathogens - Mekasha, Sophanit; Linke, Dirk (Frontiers in Microbiology, 2021)
Bacterial fish pathogens are one of the key challenges in the aquaculture industry, one of the fast-growing industries worldwide. These pathogens rely on arsenal of virulence factors such as toxins, adhesins, effectors and enzymes to promote colonization and infection. Translocation of virulence factors across the membrane to either the extracellular environment or directly into the host cells is performed by single or multiple dedicated secretion systems. These secretion systems are often key to the infection process. They can range from simple single-protein systems to complex injection needles made from dozens of subunits. Here, we review the different types of secretion systems in Gram-negative bacterial fish pathogens and describe their putative roles in pathogenicity. We find that the available information is fragmented and often descriptive, and hope that our overview will help researchers to more systematically learn from the similarities and differences between the fish-pathogenic species described here.